2D in-vivo L-COSY spectroscopy identifies neurometabolite alterations in treated multiple sclerosis. (October 2019) - Quadrelli, Scott; Ribbons, Karen; Arm, Jameen; Al-iedani, Oun; Lechner-Scott, Jeannette; Lea, Rodney; Ramadan, Saadallah
Background: We have applied in vivo two-dimensional (2D) localized correlation spectroscopy (2D L-COSY), in treated relapsing relapsing-remitting multiple sclerosis (RRMS) to identify novel biomarkers in normal-appearing brain parenchyma. Methods: 2D L-COSY magnetic resonance spectroscopy (MRS) spectra were prospectively acquired from the posterior cingulate cortex (PCC) in 45 stable RRMS patients undergoing treatment with Fingolimod, and 40 age and sex-matched healthy control (HC) participants. Average metabolite ratios and clinical symptoms including, disability, cognition, fatigue, and mental health parameters were measured, and compared using parametric and nonparametric tests. Whole brain volume and MRS voxel morphometry were evaluated using SIENAX and the SPM LST toolbox. Results: Despite the mean whole brain lesion volume being low in this RRMS group (6.8 ml) a significant reduction in PCC metabolite to tCr ratios were identified for multiple N-acetylaspartate (NAA) signatures, gamma-aminobutyric acid (GABA), glutamine and glutamate (Glx), threonine, and isoleucine/lipid. Of the clinical symptoms measured, visuospatial function, attention, and memory were correlated with NAA signatures, Glx, and isoleucine/lipid in the brain. Conclusions: 2D L-COSY has the potential to detect metabolic alterations in the normal-appearing MS brain. Despite examining only a localised region, we could detect metabolic variability associated with symptoms.